How do you find exponential decay rate?
Answer
Verified
437.4k+ views
Hint:Here in this question we have to find the exponential decay rate. That is, the rate at which a population of something decays is directly proportional to the negative of the current population at time t. So we can introduce a proportionality constant. Then further applying an integration on both sides and on simplification we get the required result.
Complete step by step answer:
Exponential decay describes the process of reducing an amount by a consistent percentage rate over a period of time. It can be expressed by the formula \[y = a{\left( {1 - b} \right)^x}\] where y is the final amount, a is the original amount, b is the decay factor, and x is the amount of time that has passed. Exponential decays typically start with a differential equation of the form:
\[ \Rightarrow \,\,\dfrac{{dN}}{{dt}}\alpha \, - N(t)\]
That is, the rate at which a population of something decays is directly proportional to the negative of the current population at time t. So we can introduce a proportionality constant \[\alpha \]:
\[ \Rightarrow \,\,\dfrac{{dN}}{{dt}} = - \alpha \,N(t)\]
We will now solve the equation to find a function of \[N(t)\]:
\[ \Rightarrow \,\,\dfrac{{dN}}{{N(t)}} = - \alpha \,dt\]
\[ \Rightarrow \,\,\dfrac{{dN}}{N} = - \alpha \,dt\]
Apply integration both sides, then
\[ \Rightarrow \,\,\int {\dfrac{{dN}}{N}} = \int { - \alpha } \,dt\]
\[ \Rightarrow \,\,\int {\dfrac{{dN}}{N}} = - \alpha \int {dt} \,\]
Using the integration formula \[\int {\dfrac{1}{x}dx = \ln x + c} \] and \[\int {dx = x + c} \], where c is an integrating constant.
\[ \Rightarrow \,\,\ln N = - \alpha t + c\,\]
As we know the logarithm function is the inverse form of exponential function, then
\[ \Rightarrow \,\,N = {e^{ - \alpha \,\,t + c}}\,\]
Or it can be written as:
\[ \therefore \,\,N = A{e^{ - \alpha \,t}}\]
Where A is a constant.
Hence, the general form of exponential decay rate is \[N = A{e^{ - \alpha \,t}}\].
Note:Exponential decay describes the process of reducing an amount by a constant percentage rate over a period of time. The integration is inverse of the differentiation so to cancel differentiation the integration is applied. Likewise the logarithm is inverse of exponential. Hence by using these concepts we obtain answers.
Complete step by step answer:
Exponential decay describes the process of reducing an amount by a consistent percentage rate over a period of time. It can be expressed by the formula \[y = a{\left( {1 - b} \right)^x}\] where y is the final amount, a is the original amount, b is the decay factor, and x is the amount of time that has passed. Exponential decays typically start with a differential equation of the form:
\[ \Rightarrow \,\,\dfrac{{dN}}{{dt}}\alpha \, - N(t)\]
That is, the rate at which a population of something decays is directly proportional to the negative of the current population at time t. So we can introduce a proportionality constant \[\alpha \]:
\[ \Rightarrow \,\,\dfrac{{dN}}{{dt}} = - \alpha \,N(t)\]
We will now solve the equation to find a function of \[N(t)\]:
\[ \Rightarrow \,\,\dfrac{{dN}}{{N(t)}} = - \alpha \,dt\]
\[ \Rightarrow \,\,\dfrac{{dN}}{N} = - \alpha \,dt\]
Apply integration both sides, then
\[ \Rightarrow \,\,\int {\dfrac{{dN}}{N}} = \int { - \alpha } \,dt\]
\[ \Rightarrow \,\,\int {\dfrac{{dN}}{N}} = - \alpha \int {dt} \,\]
Using the integration formula \[\int {\dfrac{1}{x}dx = \ln x + c} \] and \[\int {dx = x + c} \], where c is an integrating constant.
\[ \Rightarrow \,\,\ln N = - \alpha t + c\,\]
As we know the logarithm function is the inverse form of exponential function, then
\[ \Rightarrow \,\,N = {e^{ - \alpha \,\,t + c}}\,\]
Or it can be written as:
\[ \therefore \,\,N = A{e^{ - \alpha \,t}}\]
Where A is a constant.
Hence, the general form of exponential decay rate is \[N = A{e^{ - \alpha \,t}}\].
Note:Exponential decay describes the process of reducing an amount by a constant percentage rate over a period of time. The integration is inverse of the differentiation so to cancel differentiation the integration is applied. Likewise the logarithm is inverse of exponential. Hence by using these concepts we obtain answers.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
The sequence of spore production in Puccinia wheat class 11 biology CBSE